Empirical Test Observations in Client-Server Systems. - Hatton, Les (Computer (00189162), 2007)
The author argues that distributing software updates via downloads from the Internet provides an opportunity for internal developers to continue testing to identify product defects. The author describes statistical analysis of the defect databases of two commercial products with similar client-server architectures, and with the disparate applications of geophysical modeling and C-language parsing. The research looked at the extent to which defects in the computational server are masked by defects in the graphical client. Empirical findings also indicated that internal developers detected about half the defects after the product had been released and before users encountered them.